PENGARUH KEEFEKTIFAN PENGENDALIAN INTERNAL, KETAATAN ATURAN AKUNTANSI, PENEGAKAN HUKUM, DAN PERILAKU TIDAK ETIS TERHADAP KECURANGAN AKUNTANSI - Muammar Rizky; Fauziah Aida Fitri (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2017)
The purpose of this research is to examine the influence of effectiveness of internal control, compliance to accounting rules, law enforcement and unethical behavior toward accounting fraud SKPA  Aceh Province. The population in this study are all agencies or departements of Aceh goverment offices and secretariat totaled 52 SKPA and was choosen randomly with simple random sampling methode into 35 SKPA. The collecting of data and information needed in this research was done by field research. The data used is primary data collected directly from the subject of research by a questionnaire form. The testing of the influences of independent variables toward dependent variables was done by using multiple linear regressions model. The results of this research shows that both partially and simultaneously, effectiveness of internal control, compliance to accounting rules, law enforcement and unethical behavior are significantly influential to the accounting fraud in SKPA  Aceh Province. Keywords: accounting fraud, effectiveness of internal control, compliance to accounting rules, law enforcement,                 unethical behavior